The Effectiveness of Basal Shoot Mechanical Leaf Removal at the Onset of Bloom to Control Crop on cv. Sangiovese (V. vinifera L.): Report on a Three-year Trial - Intrieri, C.; Filippetti, I.; Allegro, G.; Valentini, G.; Pastore, C.; Colucci, E. (South African Journal of Enology and Viticulture, 2016)
Vine basal shoot leaves are known to be the primary nutritional source for fruit set at the onset of bloom. The effectiveness of mechanical removal of this foliage at that date was tested from 2012 to 2014 to control the cropping of high-yielding cv. Sangiovese in a “Toscana rosso” TGI (Typical Geographic Indication) district in Tuscany, where the yield threshold is 16 t/ha. A tractor-mounted leaf remover featuring sideby- side rotary suction and feed rollers was employed along a 50 cm basal area of cropping shoots at the beginning of bloom; control was the usual manual thinning of clusters carried out at véraison in the same vineyard. Mechanical leaf removal eliminated about 30% of leaf area and some shoots and inflorescences, thus reducing cropping potential and even resulting in a physiological effect, as the resulting clusters were composed of lower numbers of berries and were less compact and less susceptible to mould than the control. By harvest, the defoliated vines showed higher leaf area, most likely because leaf removal at the onset of bloom may have triggered compensatory new growth, and their grapes had a higher content of soluble solids than the thinned control. While both treatments kept the yield below the 16 t/ha threshold – leaf removal at an estimated 15.1 t/ha and manual cluster thinning at 15.6 t/ha – mechanical defoliation notably reduced yearly labour input: an estimated 4 h/ha against the 38 h/ha from thinning.